FEMINISM ACCORDING TO FATIMA MERNISSI'S THINKING - Adinda Novelia Puspita (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
This study aims to find out the extent of the Islamic field in responding to issues about feminism. The method used in this study is library research with a qualitative descriptive approach. To deepen the results of this research, we take the thoughts and works of one of the women scholars known worldwide, Fatima Mernissi. In her view, Fatima Mernissi felt the need to criticize the old dogmas that discredited women's roles. Although the source or evidence comes from a legitimate source. In the end, it is necessary to re-interpret the thinking on the pieces of evidence that distinguish the role of women and men in general.